Response of Phenological Events of Aesculus indica Colebr. to Climate Change Along an Altitudinal Gradient in Kumaun Himalaya, Uttarakhand - Singh, Nandan; Mittal, Amit (International Journal of Environment, 2018)
The present study investigated the timing and duration of phenological events of A. indica in different elevational range Kumaun Himalayan forest. A total of  four sites at elevation ranging between 1,900m and 2,200m were selected and at each site 10 s were marked for observations. The phenological events, i.e. leaf bud formation, leaf bud busting, leafing, flowering bud formation, flowering bud busting, flowering, fruit/seed formation, seed fall and leaf fall were monitored. Phenological duration and asynchrony of these phenophases were determined at 10 day intervals and every 2-3 day intervals during the period of peak activities. The minimum length displayed leaf bud formation (44 days) and maximum by leaf fall (86 days) across the elevation. The environmental conditions, particularly temperature, affected the phenological patterns of A. indica. The leaf bud busting activity of A. indica was 51 days. Flowering activity started on May 1st and was extended over 76 days until July 15th. Seed fall activity was extended over 66 day across elevations. ANOVA showed the longevity of phenophases were varied significantly respective to elevations (p